2018
DOI: 10.1007/s00426-018-1035-2
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory perception and blindness: a systematic review and meta-analysis

Abstract: Anecdotal reports suggest that blind people might develop supra-normal olfactory abilities. However, scientific evidence shows a mixed pattern of findings. Inconsistent observations are reported for both sensory-driven olfactory tasks (e.g., odor threshold) and higher-order olfactory functions (e.g., odor identification). To quantify the evidence systematically, we conducted a review and meta-analysis. Studies were included if they examined olfactory function (i.e., odor threshold, odor discrimination, free od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 85 publications
(168 reference statements)
5
29
0
Order By: Relevance
“…Although early-blind individuals had a harder time to determine if two wine odors belonged to the same category, their ability to discriminate wine odors (i.e., to evaluate whether two wine odors stem from the same or from different wines) was no different from sighted controls. These results are in line with previous research in which blind individuals did not outperform sighted controls on odor discrimination tasks (Cuevas et al, 2010;Beaulieu-Lefebvre et al, 2011;Sorokowska et al, 2018), even when the tasks are more complex, as in the present study.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Although early-blind individuals had a harder time to determine if two wine odors belonged to the same category, their ability to discriminate wine odors (i.e., to evaluate whether two wine odors stem from the same or from different wines) was no different from sighted controls. These results are in line with previous research in which blind individuals did not outperform sighted controls on odor discrimination tasks (Cuevas et al, 2010;Beaulieu-Lefebvre et al, 2011;Sorokowska et al, 2018), even when the tasks are more complex, as in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…We also did not find any significant group differences with regards to free odor identification, despite a small advantage for the early-blind individuals, in line with Sorokowska (2018). We also examined whether early-blind individuals were better at generating odor Early-blind individuals show impaired performance in wine odor categorization, 17 descriptors (Burton et al, 2002), which may explain better free odor identification performance reported in some studies.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, long-term visual impairment does not seem to affect olfactory performance in comparison to vision in healthy subjects as measured by TDI testing (Luers et al 2014). Also, a recent meta-analysis concluded blind people do not have superior olfactory abilities (Sorokowska et al 2018). Therefore, possible effects of blindfolding on testing performance within this study should only be addressed with caution.…”
Section: Discussionmentioning
confidence: 62%
“…In short, the majority of evidence suggests that congenitally or early blind individuals are generally less affected by multisensory illusions. However, in contrast to audition and touch, the majority of studies in olfaction show small or, in most of the cases, no differences in olfactory abilities between sighted and blind people (e.g., odor threshold, discrimination, identification, and memory), with the only difference being in odor imagery where blind individuals outperform sighted (Cornell K€ arnekull et al, 2016(Cornell K€ arnekull et al, , 2018(Cornell K€ arnekull et al, , 2020Sorokowska et al, 2019). This suggests that blind individuals would not be able to draw on enhanced odors skills to separate verbal information from the odor percept per se.…”
Section: Introductionmentioning
confidence: 98%